RISK ASSESSMENT OF AN EMERGENCY RESPONSE PROJECT - Рожко, Станислав (SWorldJournal, 2020)
The problem of risks of the counteraction to emergency situations projects is considered. It is established that the main risks of the emergency response project are losses associated with the choice of an ineffective response option; "disruption" in term